Alcoholism sourcebook : basic consumer health information about alcohol use, abuse and alcoholism, psychological factors, family history, other influencing factors, facts and statistics, risk factors, impact on health, prevention strategies, screening and counseling, psychosocial and biomedical issues during detoxification, behavioral couples therapy, recovery and coping with alcoholism : along with facts about treatments, clinical trials and research, a glossary of related terms, and a directory of resources for additional information - Jones, Keith (Detroit, MI : Omnigraphics, Inc., 2015)
"Excessive alcohol use causes approximately 88,000 deaths each year, making it the third leading lifestyle-related cause of death in the United States. Alcohol affects every organ in the drinker's body. While moderate alcohol use can have some health benefits for adults, heavy alcohol use and binge drinking can harm the body, disrupt relationships, and lead to risky behaviors, injury, illness, or death. Furthermore, any alcohol use can cause permanent harm to underage drinkers and to the unborn children of pregnant women." "Alcoholism sourcebook, fourth edition provides readers with updated information about alcohol use, abuse, and dependence. Physical alcohol-related effects on the brain, heart, liver, pancreas, bones, nerves, lungs, stomach, kidneys, and immune system are described, and mental health issues that often accompany alcohol problems are discussed. A section on the problem of underage drinking looks at the causes and consequences of drinking among adolescents, and another section discusses the effects of alcohol use on reproductive and fetal health. Facts about alcohol's impact on families, workplaces, and communities are included, and guidance is provided for helping someone with an alcohol problem receive appropriate treatment and recovery services. The book concludes with a glossary of terms related to alcohol use and abuse and directories of resources for support and additional information."--Publisher.
Understanding alcohol : use and abuse -- Diagnosis of alcoholism -- Risk factors and prevention -- Treatment and recovery -- Clinical trials and research on alcoholism -- Additional information.
Includes bibliographical references and index.
Keywords: Alcoholism -- Popular works; Consumer education